A influência da idade na percepção de dificuldade de abertura de embalagens PET para refrigerantes - Silva, Danilo Corrêa [UNESP]; Inokuti, Élen Sayuri [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2013)
Nowadays, there is an increasing demand for subjective aspects of the interface between human beings and the products and systems that surround them, whether in the workplace or at home. This study addresses the association of age and the perception of difficulty during a simulation of opening process PET bottles for soft drinks. During the activities, the subjects exerted their maximum torque forces, trying to open five different models of these packages, and then they assigned scores for perception in a scale. The results indicate that for some models, there were differences between levels of perceived difficulty between age groups.

Atualmente, há uma crescente demanda por aspectos subjetivos da interface entre o ser humano e os produtos e sistemas que o cercam, seja em ambiente de trabalho ou doméstico. Esse estudo trata da associação da idade à percepção de dificuldade durante uma simulação do processo de abertura de embalagens PET para refrigerantes. Durante as atividades, os sujeitos exerceram suas forças de torque máximas para tentar abrir cinco modelos diferentes dessas embalagens, e então atribuíram valores em uma escala de percepção. Os resultados apontam que, para alguns modelos, houve diferenças entre os níveis de dificuldade percebida entre faixas etárias.
The influence of age in perception of pet packaging opening difficulty soft
Keywords: Design; Packaging; Ergonomics; Perception; Soft drinks; Design; Embalagem; Ergonomia; Percepção; Refrigerantes